Estimasi Emisi Kendaraan Ringan pada Ruas Jalan Perintis Kemerdekaan Kota Makassar - S.N.J. Patunrangi; A.I.N.K. Kadir; M. Sutrisno (Civil Engineering Department, Tadulako University, 2023)
Population growth is increasingly demanding economic growth accompanied by the need for transportation as facilities of movement person and goods. The increase of transport it is not balanced with the right policies will cause various problems appertain the increasing number of motorized vehicles that has an impact on the environment, namely increasing air pollution. Exhaust emissions from motorized vehicles originating from fossil fuels make impact the environment. Various studies on transportation models have been developed by many researchers, various transportation models can also estimate emissions from motorized vehicles included MOVES and IVEM. The aim of this study is to analyze whether there are differences between the results of the emission estimation model in the MOVES and IVEM programs. The method used is using a driving cycle, where the vehicle is tracking on the highway using GPS second per second. Tracking is carried out on the Perintis Kemerdekaan road with a starting point of KM 7.75 to the end point of KM 13.12 as well as for the opposite direction. Tracking done at peak hours of 7-10 am, 11-14 noon, and 11-14 afternoon. The results showed that the concentration of Nox emissions was higher in the MOVES model data analysis than the IVEM model, as the CO emission concentration in the morning and evening was higher in the MOVES model and the CO emission concentration during the day was higher in the IVEM model. Statistically with the t test, the result is 0.13 where the result of the CO concentration for the MOVES and IVEM models are the same and for the t test the NOx concentration is 0.008 that the results of the analysis of the IVEM and MOVES models for NOx are not the same.